Pragmatic Functions of Imperatives in Conversation - Káninská, Petra (Univerzita Pardubice, 2016)
This paper focuses on functions of imperatives in English conversation from the viewpoint of pragmatics. The theoretical part deals discusses morphosyntactic features of imperatives and types of imperative constructions. Further, functions of imperatives are described in the context of speech acts and politeness strategies. The practical part is concerned with analysis of imperative constructions in a selected TV series and with their interpretation with regard to the context.
Pragmatické funkce imperativu v konverzaci
Keywords: imperativ; ilokuční síla; pozitivní zdvořilostní strategie; přímé vyjádření imperativu; direktivní řečový akt; imperative; illocutionary force; positive politeness strategy; bald-on-record imperative directive speech act